An index of nonlinear HRV as a proxy of the aerobic threshold based on blood lactate in elite triathletes - Rogers, B.; Berk, S.; Gronwald, T. (Sports, 2022)
Background: A non-linear index of heart rate (HR) variability (HRV) known as alpha1 of Detrended Fluctuation Analysis (DFA a1) has been shown to change with increasing exercise intensity, crossing a value of 0.75 at the aerobic threshold (AT) in recreational runners defining a HRV threshold (HRVT). Since large volumes of low intensity training below the AT is recommended for many elite endurance athletes, confirmation of this relationship in this specific group would be advantageous for the purposes of training intensity distribution monitoring. Methods: Nine elite triathletes (7m, 2f) attended a training camp for diagnostic purposes. Lactate testing was done with an incremental cycling ramp test to exhaustion for the determination of the first lactate threshold (LT1). Concurrent measurements of cardiac beta-to-beat intervals were performed to determine the HRVT. Results: Mean LT1 HR of all 9 participants was 155.8 bpm (±7.0) vs HRVT HR of 153.7 bpm (±10.1) (p = 0.52). Mean LT1 cycling power was 252.3 W (±48.1) vs HRVT power of 247.0 W (±53.6) (p = 0.17). Bland Altman analysis showed mean differences of -1.7 bpm and -5.3 W with limits of agreement (LOA) 13.3 to -16.7 bpm and 15.1 to -25.6 W for HR and cycling power respectively. Conclusion: The DFA a1 based HRVT closely agreed with the LT1 in a group of elite triathletes. Since large volumes of low intensity exercise are recommended for successful endurance performance, fractal correlation properties of HRV shows promise as a low cost, non-invasive option to that of lactate testing for identification of AT related training boundaries